2013
DOI: 10.1016/j.adolescence.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the role of body dissatisfaction in the gender differences in depressive symptoms and disordered eating: A longitudinal study during adolescence

Abstract: This study was aimed at examining whether body dissatisfaction in early adolescence contributes to the development of gender differences in depressive symptoms and disordered eating across early to mid‐adolescence, testing both a mediation hypothesis (higher levels of body dissatisfaction in girls, provided body dissatisfaction is a predictor of psychopathology beyond the effect of gender) and a moderation hypothesis (more detrimental effect of body dissatisfaction in girls). A community‐based sample initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 120 publications
(115 reference statements)
3
62
1
3
Order By: Relevance
“…19 In 2014, a Spanish study by Ferreiro et al found that teens who had body image dissatisfaction (BID) were at increased risk of depressive symptoms. 8 Another study, conducted in 2014 by Blow et al in a sample of 160 Hispanic college students in Texas, found the same association. 14 On the other hand, a study conducted in Brazil by Fortes et al in 2015 on 407 young people showed no association between these variables.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…19 In 2014, a Spanish study by Ferreiro et al found that teens who had body image dissatisfaction (BID) were at increased risk of depressive symptoms. 8 Another study, conducted in 2014 by Blow et al in a sample of 160 Hispanic college students in Texas, found the same association. 14 On the other hand, a study conducted in Brazil by Fortes et al in 2015 on 407 young people showed no association between these variables.…”
Section: Introductionmentioning
confidence: 66%
“…6,7 According to research conducted in various countries, including the United States, Jamaica, and Spain, distorted body image could be a risk factor for developing depressive symptoms. [8][9][10][11][12][13][14][15] Body image is defined as ''a concept that one has of their own shape, size, body mass and parts.'' 16 Misperceptions can have a great impact on adolescents 2 due to the extreme measures they might then take in pursuit of the ''ideal image.''…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that body dissatisfaction can trigger low self-esteem and an increase in depressive symptoms, which are in turn linked to psychological problems (Ferreiro, Seoane, & Senra, 2014;Raich, 2001;Sarwer, Dilks, & Spitzer, 2012) such as interpersonal anxiety. As a result, anyone who rejects themselves is likely to think that they will be rejected by others (Raich, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Linked to dissatisfaction and BDD are eating disorders (such as bulimia nervosa and/or anorexia nervosa), muscle dysmorphia and mood disorders, among other conditions (Ferreiro et al, 2014; Body image is a construct defined by Schilder (1983) as the "mental representation we create of our body" (p. 15). Schilder advocates a biopsychosocial approach that takes the following into consideration: biological aspects such as age, gender and BMI; psychological aspects such as body satisfaction/dissatisfaction; and sociocultural aspects such as socioeconomic status, the weight of one's peers, parents' preoccupations with their children's weight and dissatisfaction with one's own body.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Failure to consume a nutritionally balanced diet at this decisive point in life not only arrests linear growth but also influences the psychomotor functioning of adolescents. 6 Numerous studies and reports [7][8][9][10][11] revealed that adolescents are at a greater risk of nutritional deficiencies and disorders due to their rapid body growth, unhealthy eating habits, psychological, mental and emotional pressures associated with body dissatisfaction and temptations to have a slimmer body. Adolescents also tend to suffer from a variety of eating disorders i.e., anorexia nervosa, bulimia nervosa as well as depression, anxiety and psychological stress.…”
mentioning
confidence: 99%